2020
DOI: 10.36380/jwpr.2020.12
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mutation in the Promoter Region of Avian Uncoupling Protein3 Associated with Feed Efficiency and Body Composition Traits in Broiler Chicken.

Abstract: The Avian Uncoupling Protein (avUCP) belongs to the mitochondrial anion transporter family. It has a pivotal homeostatic mechanism that associated with energy regulation and lipid metabolism. The avUCP considered as a candidate gene for chicken growth-related traits according to its predominant expression is in skeletal muscle. To address genetic distance pattern of UCP3 between mammalian and avian species, sequence similarity analysis using the protein alignment of UCP3 identified the high amino acid identity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…PCR-SSCP has been used for several traits of animals such as wool characteristics [23], milk production traits [24], profile of sheep fatty acids [25], detection of Escherichia coli in the black swan [26], growth and carcass traits in lambs [27], reproductive traits in cattle [28], egg production traits in hens [29], body weight traits on chicken [30][31][32], gene study for fat-tailed and nonfat-tailed sheep [33], serotyping dichelobacter nodosus [34], mitochondrial diversity role in the productivity of quails [35], miR-9 gene affects litter size in goats [36], mutations in porcine [37], prolactin gene and association with egg production in ducks [38], wool fibre diameter in ewes [39], lactoferrin gene affects milk content in buffaloes [40], milk traits in yaks [41], association between MyoG gene and egg quality [42].…”
Section: Animalsmentioning
confidence: 99%
“…PCR-SSCP has been used for several traits of animals such as wool characteristics [23], milk production traits [24], profile of sheep fatty acids [25], detection of Escherichia coli in the black swan [26], growth and carcass traits in lambs [27], reproductive traits in cattle [28], egg production traits in hens [29], body weight traits on chicken [30][31][32], gene study for fat-tailed and nonfat-tailed sheep [33], serotyping dichelobacter nodosus [34], mitochondrial diversity role in the productivity of quails [35], miR-9 gene affects litter size in goats [36], mutations in porcine [37], prolactin gene and association with egg production in ducks [38], wool fibre diameter in ewes [39], lactoferrin gene affects milk content in buffaloes [40], milk traits in yaks [41], association between MyoG gene and egg quality [42].…”
Section: Animalsmentioning
confidence: 99%
“…It thus may have the potential to be considered the missing link in the chain of whole-body energy homeostasis in chickens. The avUCP is a homolog with more than 70% protein sequence similarity with mammalian UCP3 and UCP2 , harboring two conserved regions of the mitochondrial carrier and ADP/ATP transporter translocase ( 1 , 2 ). The avUCP gene was first identified in 2001 after screening a hummingbird skeletal muscle cDNA library ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…avUCP has also been suggested to be involved in cell metabolism. Several studies have identified polymorphism of the avUCP gene that is associated with fat metabolism, growth, feed intake, and exposure to abiotic stress conditions ( 2 , 21 , 22 ). Additionally, it was also revealed that the upregulation of avUCP can result in the down-regulation of reactive oxygen species (ROS) production in the skeletal muscle of fasted chickens ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation